Pemberdayaan dan Peningkatan Potensi Pertanian di Desa Nginamamu Kecamatan Wolomeze Kabupaten Ngada - Igniosa Taus; Umbu A. Hamakonda; Victoria C. Lea; Oriensi Y. K. Teftae; Antonius Dolu; Mikael lauda Pati; Victoria A. Puspita; Marten U. Kaleka (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
Nginamanu Village has superior potential in the agricultural sector and the livestock sub-sector which is the main source of income for the community. This potential has not been utilized optimally due to the limited knowledge and skills of the community in the management of their natural resources. This Community Service Activity (PKM) aims to empower the farming community in Nginamanu Village and improve the quality of human resources to be able to manage and develop local potential in a more productive and sustainable manner. This activity involved students from the Agrotechnology and Agribusiness Study Program, accompanied by lecturers from both study programs as facilitators and resource persons. The methods used in this activity include community empowerment through a participatory approach, the formation of local work teams, community-based training, and ongoing mentoring in the field. The training materials include modern agricultural cultivation techniques, agribusiness management, processing of agricultural products, and institutional capacity building of farmer groups. In addition, training was also provided on the development of environmentally friendly household-scale farms. The results of the activities show a significant increase in community knowledge and skills, which is reflected in increasing agricultural productivity, the use of appropriate technology, and growing awareness of the importance of efficient farm management. The community is able to apply the training materials through direct practice on their respective farms. On the other hand, this activity is a medium for the implementation of knowledge and field experience for students, strengthening their active involvement in village development. This PKM activity proves that synergy between universities and village communities can be a driving force in improving welfare based on local potential.